Analisis Permintaan dan Persaingan Minyak Kelapa (Crude Coconut Oil) Indonesia di Pasar Internasional (Jurnal Agribisnis Indonesia, 2020)
As the world's largest coconut producer, Indonesia has the opportunity to become the main exporter of processed coconut products. Crude coconut oil (CCO) is one of the leading processed coconut products which is currently increasing in demand. In the export market of crude coconut oil, Indonesia deals with intense competition with other crude coconut oil exporters. The objective of this study was to analyze the factors that influence the import demand of Indonesian crude coconut oil and competition between Indonesian crude coconut oil with other crude coconut oil exporters in the international market. The analytical method used was the Almost Ideal Demand System (AIDS). The results showed that the factors that influence import demand of Indonesian crude coconut oil in the international market were various and Indonesian crude coconut oil could compete with crude coconut oil from Philippine in the US and German markets. The competition was indicated by the positive cross elasticity value (substitution). The decreasing price of crude coconut oil of Philippine will reduce the market share of Indonesian crude coconut oil. Therefore, Indonesia needs to improve its marketing strategy and increase crude coconut oil production to increase Indonesian crude coconut oil exports.